Efecto del etileno en la inducción de resistencia en las plantas. - Collaguazo Martínez, Carlos Gabriel (2025)
The effect of ethylene on the induction of resistance is a method that promises a new control of pests and diseases by making the plant resistant to attacks by these agents. The following research work is carried out, so it is of utmost importance to collect information on the effects of ethylene on the induction of plant resistance. The purpose of this work is to characterize the effect of ethylene on induction in plants in the Los Ríos region. The results showed that ethylene increased antibody production and reduced the severity of the disease. They also demonstrated that the application of ethylene must be carried out very carefully and always taking into account the appropriate concentrations for each plant. In this research study, we have investigated successful cases to induce greater antibody production and reduce disease severity compared to common controls. Furthermore, a higher expression of defense genes was observed in plants treated with ethylene. In conclusion, the study demonstrated that ethylene can induce resistance in plants by activating natural defense mechanisms. We met plants that had a favorable response in the induction of ethylene for plant resistance, and thus know the benefits it provides in plants.